RELEVANSI TERM KAFA’AH PADA PERNIKAHAN ADAT BATAK MANDAILING DI TABAGSEL - Sawaluddin Siregar; Misbah Mardia (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
In the Mandailing community in Tabagsel, they tend to ignore the element of estrangement when looking for a life partner for their child. Most of those who marry off their sons and daughters without sequencing become households with broken homes, often resulting in divorce. This research is categorized as descriptive qualitative research. The data is taken from predetermined informants (people who marry without kafa'ah, village heads, traditional leaders, and in the form of books, the results of previous research that are relevant to the focus of the study. With data collection techniques through observation, interviews, and documentation. The findings in the field indicate that the mandailing community in Southern Tapanuli. Not paying attention to the kafa'ah factor in marriage. Many are married without kafa'ah in the household. Often found discrepancies, fights, cornering each other, not even a little lead to a court (divorce) due to not paying attention to the element of kafaah in question. Through this research, it is hoped that in the future the community will consider the kafaah element in marriage. Because with kekufu in a marriage it will be easy to make the family sakinah, mawaddah warahmah, my home is my heaven